Civic Space: Shrinking from the outside in? - Sogge, David (Iberoamerican Journal of Development Studies, 2020)
Restrictions on NGOs and others promoting civil liberties have caused alarm about «shrinking civic space» perpetrated by their domestic regimes. Yet because most camps in the world’s civil societies are left unmolested (indeed many are growing) and because non-domestic sources of constraint often play decisive roles, there are reasons to re-think the issues and ask how, and for whom, civil spaces are shaped. This exploratory article draws attention to forces set in motion from central, transnational levels that affect civic spaces: securitization; constraints on organized labour; marketization; transnational non-state actors; citizen disengagement driven by state retrenchment; and social media. As problematized in most policy, activist and scholarly writings, outside forces affecting civic space for emancipatory camps are often ignored, despite their being more susceptible to counteraction from outside than are repressive regimes. These issues await deeper investigation and discussion.